Biofeedback treatment of proctogenic constipation in adults - A. Yu. Titov; O. M. Birukov; O. Yu. Fomenko; M. A. Voynov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study efficacy of biological feedback treatment (BFT) at proctogenic constipation in adult patients.Material and methods. Overall 30 patients with proctogenic constipation and dyssynergia of pelvic floor muscles i.e. spasm of puborectalis muscle were included in original study and treated by BFT method. Mean age of patients was 31,2±9,8 year, men to women ratio was 1:5.Results. During treatment decrease in difficulty to defecate according to Rome-III criteria was observed in 22 (73,3%) patients. The other 8 (26,7%) patients demonstrated no improvement. According to subjective assessment of rectal evacuatory function by questioning before and after BFT statistically significant reduction of proctogenic constipation symptoms was revealed. By the data of objective investigation (profilometry and electromyography) signs of dyssynergia of pelvic floor muscles were revealed in no patient.Conclusions. The biological feedback is effective treatment method for proctogenic constipation, allowing to reduce symptoms in 73,3% of patients and to correct dyssynergia of pelvic floor muscles in all cases.